GLI1::FOXO4-rearranged kidney tumors: a potentially distinct renal subtype within the spectrum of GLI1-altered tumors - Pancsa, Tamás; Klubíčková, Natálie; Dashti, Nooshin K; Machado, Isidro; Llombart-Bosch, Antonio; Linos, Konstantinos; Mosaieby, Elaheh; Vaněček, Tomáš; Maňáková, Lenka; Michal, Michal; Michal, Michael (Virchows Archiv, 2025)
Pathogenic alterations, namely, fusions and amplifications, of the GLI1 gene have been identified in various mesenchymal tumors, including pericytoma with t(7;12), plexiform fibromyxoma, gastroblastoma, and other malignant mesenchymal neoplasms arising in the soft tissues, as well as in various visceral organs. However, only three cases of GLI1-rearranged renal tumors have been reported to date, comprising two low-grade spindle cell tumors with GLI1::FOXO4 fusion along with one GLI1-rearranged case with an unknown fusion partner. In this study, we analyzed three cases with GLI1::FOXO4 fusion and overlapping morphology. One of the cases was reported previously, but an extended clinical and immunohistochemical information is provided. The studied cases occurred in 2 female and 1 male patients aged 35, 55, and 62 years (mean 51 years). All three tumors affected the renal parenchyma and grew as unencapsulated but well-circumscribed solid masses containing occasional entrapped and dilated renal tubules. The tumor cells were organized in cords, nests, or fascicles, had a round to spindled shape, and exhibited only mild nuclear atypia and minimal mitotic activity. They had a sparse eosinophilic to clear cytoplasm and were embedded in myxocollagenous stroma. Immunohistochemically, all cases expressed GLI1 (albeit with variable intensity) and harbored GLI1::FOXO4 fusion. All three patients were treated solely by complete surgical excision. Case 1 was alive with unknown disease status, case 2 was alive without evidence of disease, and case 3 died of unrelated causes. Our study doubles the number of reported cases with GLI1::FOXO4 fusion. The so far absolute predilection of this fusion for renal tumors, coupled with the absence of reports of other GLI1 fusions in tumors of the kidney, might indicate the potential existence of a distinct renal subtype with morphological features similar to other GLI1-altered tumors. All four reported cases had an uneventful follow-up which, together with their low-grade morphological features, suggests that these tumors might have a favorable prognosis.
Keywords: dospělí; proteiny buněčného cyklu; nádorové biomarkery; nádory ledvin; Forkhead Transcription Factors; Zinc Finger Protein GLI1; Biomarkers, Tumor; genová přestavba; Humans; Gene Rearrangement; lidé středního věku; Kidney Neoplasms; Middle Aged; imunohistochemie; mužské pohlaví; Immunohistochemistry; Adult; Cell Cycle Proteins; protein Gli1; ženské pohlaví; forkhead transkripční faktory; lidé; Male; Female